Sharia as informal law: lived experiences of young Muslims in Western societies - Yilmaz, Ihsan (Routledge, 2025)
"This book takes a comprehensive approach to investigate how Sharia influences and manifests in the everyday lives of Muslims, aiming to unravel the meaning and relevance of Sharia-driven laws and practices in English-speaking Western societies. By focusing on the grassroots level, it provides a deeper understanding of the lived experiences of Muslims and their relationship with Sharia. The presence of Muslims in Western countries has a long history, with recent waves of migration and conversions contributing to their increasing numbers. This study recognizes the diverse nature of the Muslim community, comprising both migrants and local converts, who have become integral parts of the pluralistic fabric of multicultural societies. The research draws on in-depth interviews with 122 young Muslim individuals from diverse backgrounds, representing three different Western countries: Australia, the United States, and the United Kingdom. This deliberate selection of participants allows for a broader exploration of the Muslim community and showcases the inherent diversity of opinions, interpretations, and practices regarding Sharia. This approach moves beyond abstract discussions and theoretical debates, providing concrete insights into the practical implications of Sharia for young Muslims in their respective Western contexts. The book also sheds light on the evolving landscape of information and knowledge acquisition. It explores how young Muslims access and seek knowledge in the twenty-first century, recognizing the impact of changing sources and modes of information on their religious practices and beliefs. This aspect adds a valuable dimension to the study, capturing the dynamic nature of knowledge dissemination and acquisition among young Muslims in Western societies. The book will be fascinating reading for academics, researchers and policy-makers working in the areas of Law, Political Science, Minority Studies, Religious Studies and Islamic Studies"--